Conceptualizing Flow for Content Marketing Effectiveness - Chakravorti, Samit (Journal of Marketing Development and Competitiveness, 2023)
The paper explores and consolidates the concept and experience of flow regarding its implications for content marketing in the digital marketplace. Technology-supported content marketing in the e-market has become increasingly important for customer satisfaction. The flow experience has also been shown to be an important aspect of online consumer behavior and linked to beneficial market outcomes. At the same time, the conceptualizations of flow have been evolving and no clear established framework for it exists. Through a qualitative review of current academic and practitioner research on the usage of content marketing for engaging consumers the paper consolidates findings. It creates a framework to advance the conceptualization of flow for content marketing and an understanding of how brand content usage and promotions in the digital sphere can determine the characteristic of flow and work with it to positively impact beneficial market outcomes.